FORMULATION AND IN VITRO EVALUATION OF BILAYER TABLET OF ATENOLOL FOR BIPHASIC DRUG RELEASE - Parashar, Tarun; Singh, Nardev (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present research work, the aim was to prepare the bilayer tablet of atenolol for biphasic drug release to improve its bioavailability and absorption in the lower gastrointestinal tract. Methods: In the formulation of immediate release crospovidone, croscarmellose sodium, and sodium starch glycolate was used as super disintegrate and was directly compressed. For a sustained release portion different grade hydroxypropyl methylcellulose (HPMC) K4M, HPMC K15M, gum tragacanth, gum acacia, guar gum, and ethyl cellulose. Preformulation studies were performed before compression. The compressed bilayer tablets were evaluated for weight variation, dimension, hardness, friability, drug content, disintegration time, and in vitro drug release using USP dissolution apparatus type 2 (paddle). Results: The formulation IR3 showed 95% drug release in 30 min, and regression coefficient value (r2) value was found to be 0.994 suggesting first-order drug release kinetics. The F9 formulation using HPMC K15M and gum acacia (1:1) showed 91.20% drug release at the end of 12 h, and regression coefficient value (r2) was 0.992 suggesting zero-order drug release kinetics. Formulation IR3F9 showed faster drug release for bilayer tablet containing 5%w/w crospovidone in immediate release layer and HPMC and guar gum (1:1) in sustained release. Formulation IR3F9 showed swelling index 206%, floating lag time was found to be 2 min and total floating time up to 12 h. Conclusion: The formulation IR3F9 showed a faster drug release profile among the others in the preparation of the atenolol bilayer tablet. Hence, it was considered as an optimized formulation.